QUANTITATIVE ANALYSIS OF ENTEROCOCCI ISOLATED FROM DAIRY PRODUCTS - Zelena , Liubov; Tkachuk, Nataliia; Okhmat , Olena; Nevmyvaka , Sabrina (Biota. Human. Technology, 2022)
Purpose of the work. To evaluate the number of enterococci in the dairy products of industrial manufacturing. Methodology. Molecular-genetic methods were used to analyze enterococci in milk, kefir and sour cream samples. Metagenomic DNA was isolated from each product and used for amplification. PCR with specific primers to Enterococcus genus was carried out to amplify specific genome region and to detect enterococci in dairy products. Quantitative PCR (qPCR) with SYBR Green dye solution was performed to enumerate Enterococcus bacteria presented in three milk products. The melting curve analysis was used to define the specificity of amplification. The genome-equivalent values of enterococci in milk, kefir and sour cream were calculated using the standard curve analysis. Scientific novelty. In the present research the quantitative analysis of enterococci in the three milk products of industrial manufacturing was conducted using metagenomic DNA and qPCR-analysis. There were no significant differences of enterococci number between dairy products. Conclusions. The development of molecular-genetic methods and approaches gives a possibility to estimate the number of enterococci in dairy products by culture-independent way. The results suggested that similar amount of enterococci in all three dairy products can be due to their industrial production and using the same preservation agents. Although the genotyping and species identification of Enterococcus should be performed in the next researches. The fermented milk products have an important and in general beneficial effect on human health. Despite qualitative and quantitative variability of microorganisms comprising the composition in milk products, lactic acid bacteria represent the most numerous group. The ambiguous features characterize bacteria belonging to Enterococcus genus: they contribute to the specific flavor and taste of dairy products and can be used as a probiotic and adjunct starters but, at the same time, they can be the source of virulence factors and be an indicator of poor hygienic conditions during production. Thus, it is important to perform quantitative analysis and control of enterococci in dairy products.